Board characteristics and financial performance of banks listed on frontier stock markets in East Africa. A panel analysis - Anthony Magoma; Enid Ernest; Ernest Kasheshi (Cogent Business & Management, 2024)
This study investigates the impact of board characteristics on the financial performance of 14 listed banks in Kenya, Tanzania, and Uganda. We use 84 firm-year observations of 14 listed banks from three stock markets in East Africa, namely Dar es Salaam Stock Exchange (DSE), Nairobi Security Exchange (NSE), and Uganda Security Exchange (USE) for a six-year period that is 2017–2022. The accounting measure of financial performance was the net interest margin (NIM). This study used a fixed-effects panel analysis model to test the hypotheses. The empirical results reveal that board financial expertise positively and significantly influences financial performance. This implies that an increase in the proportion of board members with financial and accounting backgrounds increases bank performance. On the other hand, the proportion of foreign directors decreased bank performance as the variable exerted a negative and significant effect on bank performance. The results suggest that board structure has an important role to play in the governance of listed banks in East African frontier stock markets.
Keywords: 650; Board characteristics; financial performance; agency theory; resource dependency theory